2022
DOI: 10.1080/20008066.2022.2141510
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mental health of university students faced with different lockdowns during the coronavirus pandemic, a repeated cross-sectional study

Abstract: Background: Studies have highlighted the impact of the COVID-19 pandemic on the mental health of university students. However, little is known about the psychological impact of successive lockdowns on this population. Objectives: To assess the prevalence of psychological distress in a student population during the first two lockdowns linked to the COVID-19 pandemic, and to stratify them by subgroup. Methods: We used a repeated cross-sectional study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…While the mental health impact of the COVID-19 pandemic on healthcare workers has been a focal point of investigation, other at-risk populations including students (Ali et al, 2021 ; Bountress et al, 2022 ; Essadek et al, 2022 ; Pat-Horenczyk et al, 2021 ), refugees (Akhtar et al, 2021 ; Liddell, Murphy, et al, 2021 ; Liddell, O'Donnell, et al, 2021 ), persons exposed to violence (Birkeland et al, 2021 ; Gibert et al, 2021 ) or past childhood adversity (Clemens et al, 2021 ), and military personnel (Richardson et al, 2022 ) have also been a nidus for research on mental health outcomes. A multitude of studies and reviews have highlighted the ubiquitous negative mental health effects of the pandemic (Nochaiwong et al, 2021 ; Zhao et al, 2021 ) and lockdowns (Chen et al, 2022 ), including PTSD (Bonati et al, 2022 ; (Laurent et al, 2022 ) Yuan, et al, 2021 ), adjustment disorders (Ajdukovic et al, 2021 ; Dragan et al, 2021 ; Liddell, O'Donnell, et al, 2021 ; Lotzin et al, 2021 ; Shiffman et al, 2023 ), substance use disorders (Patel et al, 2023 ), and even transient psychoses (Loehde & Novakovic, 2021 ).…”
Section: Impact Of the Pandemic On Community Populations Students Vet...mentioning
confidence: 99%
See 2 more Smart Citations
“…While the mental health impact of the COVID-19 pandemic on healthcare workers has been a focal point of investigation, other at-risk populations including students (Ali et al, 2021 ; Bountress et al, 2022 ; Essadek et al, 2022 ; Pat-Horenczyk et al, 2021 ), refugees (Akhtar et al, 2021 ; Liddell, Murphy, et al, 2021 ; Liddell, O'Donnell, et al, 2021 ), persons exposed to violence (Birkeland et al, 2021 ; Gibert et al, 2021 ) or past childhood adversity (Clemens et al, 2021 ), and military personnel (Richardson et al, 2022 ) have also been a nidus for research on mental health outcomes. A multitude of studies and reviews have highlighted the ubiquitous negative mental health effects of the pandemic (Nochaiwong et al, 2021 ; Zhao et al, 2021 ) and lockdowns (Chen et al, 2022 ), including PTSD (Bonati et al, 2022 ; (Laurent et al, 2022 ) Yuan, et al, 2021 ), adjustment disorders (Ajdukovic et al, 2021 ; Dragan et al, 2021 ; Liddell, O'Donnell, et al, 2021 ; Lotzin et al, 2021 ; Shiffman et al, 2023 ), substance use disorders (Patel et al, 2023 ), and even transient psychoses (Loehde & Novakovic, 2021 ).…”
Section: Impact Of the Pandemic On Community Populations Students Vet...mentioning
confidence: 99%
“…Factors such as low family socioeconomic status, living in rural areas, knowing someone who was infected with COVID-19, and being a family member or friend to a healthcare worker, were strongly associated with poorer mental health outcomes (Elharake et al, 2023 ). In a survey early in the pandemic of more than 19,000 French university students, conducted over three successive stages (lockdown, the lifting of lockdown, and second lockdown), successive lockdowns worsened mental health, especially among PhD students; in contrast, there was a significant reduction in depression, anxiety, and psychological distress when the lockdown was lifted (Essadek et al, 2022 ). Once again, these findings underline the importance of identifying risk groups for early preventative efforts.…”
Section: Impact Of the Pandemic On Community Populations Students Vet...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, young students facing financial uncertainty or insecurity were reported to have more symptoms of anxiety and depression [ 8 ], as well as suicidal ideation [ 9 ]. The mental health of students living alone has also been shown to be significantly impacted by the pandemic [ 10 ]. These findings concur with the results of previous studies, highlighting the particular vulnerability of young people in precarious situations to psychological distress [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with the COVID-19 pandemic, the psychological state of college students has been dramatically impacted. Many scholars' studies during the crisis have confirmed that the COVID-19 pandemic had a huge negative impact on the psychological state of college students, which was usually manifested as anxiety, depression, and a small number of suicidal tendencies [5][6][7]. These mental states were a general trend.…”
Section: Introductionmentioning
confidence: 99%